Socio-demographic and antenatal care-related factors associated with early post-partum family planning use in Ethiopia: evidence from Ethiopian Demographic and Health Survey 2016 data - Asratie, Melaku Hunie; Tesema, Getayeneh Antehunegn; Chilot, Dagmawi; Aragaw, Fantu Mamo; Merid, Mehari Woldemariam; Belay, Daniel Gashaneh (Frontiers in Global Women's Health, 2023)
-Initiation of family planning in the early Ppost-partum period is thea strategic move to avert the huge numbers of maternal, neonatal, and child mortality due to the bad consequences of short interbirth interval and complications of unintended pregnancy. Despite, this great role , information is scant about the effect of content, timing, and the number of antenatal care on early initiation of post-partum family planning in Ethiopia.Objective: -This study was aimed to assess the association of antenatal care services withon the early initiation of post-partum family planning in Ethiopia.Methods: -The study was based on Ethiopian demographic and health survey 2016 data, which was a cross-sectional survey from 18 th of January 2016 to 27 th of June 2016. A total weighted sample size of 2920 post-partum women was included. A multilevel logistic regression model was used. Vvariables with a p-value of ≤0.2 in the bivariable multilevel analysis were taken to multivariable multilevel analysis. An adjusted odds ratio with a 95% confidence interval was used and variables with a p-value of <0.05 were considered as statistically significant for the outcome variable.Results: -Early initiation of post-partum family planning was 20.4%. Women with at least 4 ANC visits (Adjusted Odds Ratio (AOR=1.31; CI 1.12-2.32), women who started ANC within the first trimester (AOR=1.25; CI 1.10-2.23), complete routine antenatal care (AOR=1.11; CI 1.01-2.03), post-natal care (AOR=1.45; CI 1.19-1.87), resumption of menses (AR=1.67; CI 1.18-1.93), urban residency (AOR=2.14; CI 1.18-2.51), and high community women education (AOR=1.71; CI 1.51-2.11) were variables significantly associated with early initiation of postpartum family planning.Conclusions: -Early initiation of post-partum family planning in Ethiopia was too low.Attention needs to be given to the quality of antenatal care, post-natal care, resumption of menses, residency, and community level education of women to increase the prevalence of early initiation of post-partum family planning in Ethiopia. Therefore, the government should design a program targeting the quality of antenatal care in rural communities, considering women without menses, and scale-up educated women at the community level to scale up the culture of early initiation of post-partum family planning and end with reduced maternal, neonatal, and child mortality.